THE MOTIVE OF MADNESS IN THE NOVELS OF EDGAR ALLAN POE - Yuldasheva Sabina Yusufovna (Western European Studies, 2024)
E A Poe called romantic and rationalist. He miraculously combines thin and romantic soul, with all its experiences, feelings and longing, and strict logical mind that does not believe in inspiration, it calculates every move in advance and contemplating the effects of which should make an impression on the reader. The personality of Edgar Allan Poe is built on contradictions. It is natural to assume that in his work will also be viewed by connecting the rational and the irrational. This article is devoted to the analysis of one aspect of the philosophy of art of the American writer - motivated by madness, which is the basis of a much more complex and, in our view, the fundamental concepts of Poe's creativity - duality is realized through the motif of the border
Keywords: Edgar Allan Poe; the motive of madness; the motive of border